LEARNING IN THE COVID-19 PANDEMIC - Safaringga, Helen (Universitas Negeri Medan, 2024)
The Covid-19 pandemic resulted in a remarkable change in learning activities, where all levels of education had to be transformed in order to adapt to learning from home through online media. This study aims to find out how to learn on the Covid-19 pandemic for students, schools, and people. This research was conducted with literature research. The source of research data is obtained from articles and publication journals collected using documentation techniques. Analysis techniques using content analysis of literature and articles that are the source of research data. The results showed that in the practice of implementing online learning, many obstacles occurred both from students, teachers, and parents. These constraints make online learning less effective Keywords: Pandemic; Covid-19; learning; online